Efektivitas Penerapan Pembelajaran Media Ular Tangga Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Disekolah Menengah Pertama Islam Tanjung Camplong Sampang - Jumaatun Jumaatun; Muhlis Muhlis; Khoirul Anam; Faqqihul Marom; Akidatun Nashihah (Kariman: Jurnal Pendidikan Keislaman, 2024)
The effectiveness of the application of snakes and ladders media learning in increasing students' interest in learning Islamic Religious Education subjects at Tanjung Camplong Islamic Junior High School, Sampang, To determine the effectiveness of the application of snakes and ladders media learning and also to determine the increase in students' interest in learning Islamic Religious Education subjects. There are two main problems in this study, 1) How is the effectiveness of the application of snakes and ladders media in increasing students' interest in learning Islamic Religious Education subjects at Tanjung Islamic Junior High School? 2) What are the supporting and inhibiting factors for the application of snakes and ladders media in increasing students' interest in learning Islamic Religious Education subjects at Tanjung Islamic Junior High School? The research method used in this study is a qualitative descriptive approach in which the research results obtained are in the form of data collection, data sources from this study are the principal, PAI subject teachers, and also students. The data analysis was carried out using a qualitative descriptive method by reducing data, presenting data, and verifying the data obtained. The results of the research that the researcher has conducted are found that first, it is effective because students can be active in expressing their opinions and there is no longer awkwardness in expressing opinions, and students' interest in learning has increased, second, the supporting factors for the use of snakes and ladders media learning in increasing students' interest in learning in Islamic Religious Education subjects at Tanjung Camplong Sampang Islamic Junior High School are teachers who can choose media that will certainly make it easier for students to receive lesson materials because this snakes and ladders media learning is a direct / practical method so that students have the enthusiasm for learning. The inhibiting factors for the use of snakes and ladders media learning in increasing students' interest in learning in Islamic Religious Education subjects at Tanjung Camplong Sampang Islamic Junior High School are the lack of student awareness in learning, and the lack of supporting infrastructure for teaching and learning activities.